Immune Response in Preterm Infants to Hepatitis B Vaccine - Y Zahedpasha (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Nearly one third of the worlds population has serologic evidence of past or present infection with the hepatitis B virus (HBV). The newborn hepatitis B immunization is a critical strategy to reduce the global morbidity and mortality associated with hepatitis B. There are many studies in favor of less immune response to hepatitis B vaccine in preterm than term infants. This study was performed to evaluate the immune response in preterm infants to Hepatitis B vaccine.METHODS: This cohort was done on 71 preterm neonates with gestational age less than 37 weeks and birth weight equal or less than 2000 gram and 72 term neonates with gestational age equal or more than 37 weeks and birth weight equal or more thon 2500 gram. Sampling method was simple. Excluding criteria was including neonates of HBsAg positive mothers, infants who received less than 3 dose of vaccine and infants who received immunoglobulin or blood products. In both preterm and term groups sampling for anti-HBs was done and titer of >10 mIU/mL considered as immune response to hepatitis B vaccine. Two groups were compared according to gestational age, sex and birth weight. FINDINGS: Neonates in both preterm and term groups shown 100% response to vaccination. Immune response to vaccination have no correlation with gestational age (r=-0.112, p=0.182) and birth weight (r=-0.136, p=0.106). Mean anti HBS titer was 660±409.3 mIU/mL in preterm group and 565.4±567.9 mIU/mL in term group that showed no significant difference. In preterm group mean anti-HBs titer showed no significant difference (p=0.316) between low birth weight (1500-2000 gram), very low birth weight (1000-1500 gram) anal extremely low birth weight (<1000 gram) in preterm group. Mean anti-HBs titer show no significant difference between male and female (p=0.368), but in term group this difference was significant (p=0.007).CONCLUSION: In our study, immune response to hepatitis B vaccination was similar (100%) in preterm and term infants.